PERANCANGAN MODEL PERSEDIAAN BAHAN BAKU UBI UNGU PADA PRODUKSI KERIPIK UBI UNGU DENGAN METODE SIMULASI SISTEM DINAMIS - Iphov Kumala Sriwana; Nofi Erni; Rusydiana Abdullah (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Purple Sweet Potato is one of agricultural product that has been cultivated in Indonesia with high productivity. One of the processed products from purple sweet potatoes is snacks. It is the part of Fast Moving Consumer Good (FMCG) sector. The intense competition between snack industry players involves in the fluctuating demand on purple sweet potatoes chips. The uncertain demand for purple sweet potatoes chips causes a mismatch between supply of purple sweet potatoes and the actual needs. Therefore, this study was conducted to handle fluctuating demands by using dynamic system simulations to get maximum profit. Problem solving was done through two stages, namely designing optimal forecasting models and designing inventory models using dynamic system simulations. The dynamic system model consisted of two sub-models, namely the inventory sub-model and inventory costs. Inventory sub-models were analyzed based on the demand for the amount of production of purple sweet potato chips and purple sweet potato supply, using four scenarios, where scenario 1 was done without policy changes, scenario 2 used inventory control, scenario 3 used probabilistic model P and scenario 4 performed a combination of demand forecast adjustment and probabilistic model P. The simulation results in 28 periods produced different benefits from each scenario. The highest profit was obtained when planning production with scenario 4, which was a combination of forecasting method with P model with a service level of 90%, with a profit of Rp 195,288,659,301 ± 20,447,754,235. Scenario 4 can produced the highest profit because it could plan raw material optimally so that there were no high savings costs. Keywords: dynamic systems, inventory system, purple sweet potato, forecasting, probabilistic